Les implications politiques de l’orientalisme - Isabelle Mayaud (Revue d'anthropologie des connaissances)
Madama Butterfly now features in the repertoire of many European and North American stages. Composed by Giacomo Puccini, the score of this opera includes several Japanese musical motifs. Yet Puccini never made a trip to the Far East. How did he come by this information? To answer this question, we need to project ourselves into the intercontinental political and scholarly space of France at the turn of the 20th century. Our investigation highlights two routes for the circulation of cultural resources, from East to West. While the communities of classical musicology and ethnographic statistics share a classification system based on a binary opposition between the primitive (Indochinese) and the civilized (European), they also differ diametrically in the value they place on musical materials and the investments they allocate to capturing them. By unfolding the black box of scholarly activities and the social and material infrastructures that shape them and whose manufacture they in turn contribute to, this article invites us to explore the multiple dimensions of the power of scriptural infrastructures.